ACTIONS TO MINIMIZE AMMONIA EMISSION IN BROILER PRODUCTION: REVIEW - Sousa, F. C.; Tinôco, I. F. F.; Paula, M. O.; Silva, A. L.; Souza, C. F.; Batista, F. J. F.; Barbari, M. (Revista Brasileira de Engenharia de Biossistemas, 2016)
The main sources of ammonia generation are in agricultural activities, with great representation of poultry, by using feed lot systems with adoption of deep bedding on floor to retain the manure. Ammonia produced in broiler systems production generates damages to animals, humans and environment. The main source of ammonia in the manure deposited on the bed is the excreted nitrogen. With the adoption of appropriate techniques of environmental management, through of adequate ventilation and bed management, control of pH, temperature and humidity are possible significant reductions in ammonia emission, as well as with the use of additives and control the appropriate nitrogen content that is provided in the rations.